Scandinavian Foreign Direct Investment and Economic Growth of the Baltic States - Simelyte, Agne; Dudzeviciute, Gitana; Liucvaitiene, Aušra (European Journal of Sustainable Development, 2017)
International capital influences not only the growth of GDP but has impact on the other areas of life such as research and development, export or the growth of salaries. Even more, the intensity of inward foreign direct investment (hereinafter – FDI) shows the host country’s openness to foreign capital and its integration into the international market. The article analyses the significance of foreign direct investment in the country and its role in economic development. The authors explore the problems, which exist in attracting FDI. The object of research is the role of Scandinavian capital in the Baltic States. The aim of research is to measure the impact of Scandinavian foreign direct investment on the economic growth of the Baltic States. To implement the aim, the authors of the article apply bivariate correlation and Granger causality test. The research covers the period of 2000-2016. The final results reveal that the Baltic States, especially Latvia, are depended on foreign capital. This proves that the Baltic States compete for inward FDI from Scandinavia. Keywords: foreign direct investment, economic growth, Baltic States, Scandinavian FDI